2004
DOI: 10.1021/bi0487645
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Robust Monomeric Protein from a Hyperthermophile

Abstract: Equilibrium and kinetic studies were carried out under denaturation conditions to clarify the energetic features of the high stability of a monomeric protein, ribonuclease HII, from a hyperthermophile, Thermococcus kodakaraensis (Tk-RNase HII). Guanidine hydrochloride (GdnHCl)-induced unfolding and refolding were measured with circular dichroism at 220 nm, and heat-induced denaturation was studied with differential scanning calorimetry. Both GdnHCl-and heat-induced denaturation are very reversible. It was diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 52 publications
1
58
0
Order By: Relevance
“…Similar to numerous thermophilic proteins, which exhibit very slow unfolding processes, we obtained extremely small unfolding rates for the thermostable BLA originating from a mesophilic source. In contrast to reversible unfolding proteins, where either kinetic or thermodynamic stability can be the key feature in thermostabilization (40), only kinetic barriers determine thermostability for the ␣-amylases with a fast irreversible process. Based on this, mutant studies often revealed enhanced stabilities that are determined kinetically rather than thermodynamically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to numerous thermophilic proteins, which exhibit very slow unfolding processes, we obtained extremely small unfolding rates for the thermostable BLA originating from a mesophilic source. In contrast to reversible unfolding proteins, where either kinetic or thermodynamic stability can be the key feature in thermostabilization (40), only kinetic barriers determine thermostability for the ␣-amylases with a fast irreversible process. Based on this, mutant studies often revealed enhanced stabilities that are determined kinetically rather than thermodynamically.…”
Section: Discussionmentioning
confidence: 99%
“…In particular a comparison between mesophilic and thermophilic proteins was the focus of these studies. Besides some exceptions (40,42), most studies revealed significant slower unfolding rates for thermophilic proteins as compared with their mesophilic counterparts. At a reference temperature of 100°C for rubredoxin a difference in unfolding rates of 2-3 orders of magnitude was obtained (35).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, Tk-RNase HII was found to possess high kinetic stability and the T m value was found to depend on the scan rate of heating. 18 Therefore, the heat-induced unfolding experiments on Tk-RNase HII cannot be evaluated quantitatively due to kinetic stability. However, these results demonstrate that every mutant protein is destabilized against heatinduced unfolding compared with the WT protein.…”
Section: Heat-induced Unfoldingmentioning
confidence: 99%
“…[15][16][17] Tk-RNase HII is highly stable, and its stabilization mechanism is characterized by its remarkably slow unfolding. [18][19][20] It has also been reported that the *Corresponding author. E-mail address: ktakano@mls.eng.osaka-u.ac.jp.…”
Section: Introductionmentioning
confidence: 99%
“…Following transition state theory, not only DG but also the barrier height of the transition state determines the folding and unfolding rates and therefore controls protein stability with respect to the corresponding time regime. Recently it was demonstrated in some cases that a higher thermostability was accompanied by significantly smaller unfolding rates (K u ) as compared with their mesophilic homologues [8,[56][57][58]. In contrast, at least for proteins with reversible unfolding, only small differences in the (re-)folding rates (K f ) were observed [56].…”
Section: Inactivation and Unfolding Kineticsmentioning
confidence: 99%